2011
DOI: 10.1371/journal.pone.0018610
|View full text |Cite
|
Sign up to set email alerts
|

Cues for Early Social Skills: Direct Gaze Modulates Newborns' Recognition of Talking Faces

Abstract: Previous studies showed that, from birth, speech and eye gaze are two important cues in guiding early face processing and social cognition. These studies tested the role of each cue independently; however, infants normally perceive speech and eye gaze together. Using a familiarization-test procedure, we first familiarized newborn infants (n = 24) with videos of unfamiliar talking faces with either direct gaze or averted gaze. Newborns were then tested with photographs of the previously seen face and of a new o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 59 publications
(85 reference statements)
5
57
0
3
Order By: Relevance
“…These results were consistent with previous studies that showed that bidirectional associations can be automatically acquired and further demonstrated that presenting effect stimuli can automatically activate associated responses (Elsner & Hommel, 2001 aspects of the cognitive processing and/or behavioral response which take place concurrent to or immediately following it (e.g., Csibra & Gergely, 2009;Farroni, et al, 2003;Macrae, et al, 2002;Mason, et al, 2004;Senju & Csibra, 2008;Senju & Johnson, automatic mimicry of observed hand movements (Farroni, et al, 2003;Wang, Newport, & Hamilton, 2011). In addition, direct gaze captures visuospatial attention and facilitates face recognition (Guellai & Streri, 2011;Macrae, et al, 2002;Mason, et al, 2004;von Grünau, & Anston, 1995). Given these results, if the results of Experiment 1 are truly social in nature, eye contact should modulate the observed effect.…”
Section: Test Phasesupporting
confidence: 89%
See 1 more Smart Citation
“…These results were consistent with previous studies that showed that bidirectional associations can be automatically acquired and further demonstrated that presenting effect stimuli can automatically activate associated responses (Elsner & Hommel, 2001 aspects of the cognitive processing and/or behavioral response which take place concurrent to or immediately following it (e.g., Csibra & Gergely, 2009;Farroni, et al, 2003;Macrae, et al, 2002;Mason, et al, 2004;Senju & Csibra, 2008;Senju & Johnson, automatic mimicry of observed hand movements (Farroni, et al, 2003;Wang, Newport, & Hamilton, 2011). In addition, direct gaze captures visuospatial attention and facilitates face recognition (Guellai & Streri, 2011;Macrae, et al, 2002;Mason, et al, 2004;von Grünau, & Anston, 1995). Given these results, if the results of Experiment 1 are truly social in nature, eye contact should modulate the observed effect.…”
Section: Test Phasesupporting
confidence: 89%
“…In humans, even newborns prefer to look at faces with direct gazes over faces with averted gazes (Farroni, Csibra, Simion, & Johnson, 2002). In addition, even in newborns, eye contact facilitates face recognition (Guellai & Streri, 2011). Senju and Johnson (2009) propose the neural basis of such an effect of eye contact: they postulate that the subcortical pathway including the superior colliculus, pulvinar, and amygdale-which is relatively mature even in infants-rapidly detects eye contact (or socially significant stimuli), and then it regulates subsequent cortical processing in the areas to which it projects in a top-down fashion.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the suggestion of Guellai and Streri (2011) that there are diverse social functions for the act of looking. In our analysis, glance generated the least response and did not appear to serve as a form of initiation; watch appeared to be much more than a means of passively observing others and, in fact, generated response when used in tandem with other forms of language, and gaze served as a means of active and mutual engagement, often interpreted as emotional by the teachers.…”
Section: Combinations Of 'Looks'supporting
confidence: 89%
“…As Bettes (1988) asserts, timing of response is central to infant well-being. Guellai and Streri (2011) suggest that the gaze alters in different interactive settings, according to the sustained nature of the 'look' and with, or without, the accompaniment of speech. This assertion is upheld by Kidwell (2010) who, in one of the only studies of the 'look' in an early childhood education context, distinguished between 'mere looks' (glance) and 'the look' (gaze) for 12-30-monthold infants in communication with their teachers.…”
Section: The Significance Of the 'Look'mentioning
confidence: 99%
“…Nevertheless, numerous studies have revealed that babies can perceive speaking faces, photographs, objects, pictures, discriminate between large numbers, etc. (Coulon, Guellai and Streri, 2011;Féron, Gentaz, and Streri 2006;Guellai and Streri, 2011;Izard, Sann, Spelke and Streri, 2009;Meary, Kitromilides, Mazens, Graff and Gentaz, 2007;cf. Kellman and Arteberry, 1988, for a review).…”
Section: Initial Evidence In Newbornsmentioning
confidence: 99%